Resúmenes de novedades - Foro Internacional, Revista (Foro Internacional, 2024)
Luis L. Schenoni. 2024. Bringing War Back In: Victory, Defeat, and the State in Nineteenth-Century Latin America. Cambridge, Reino Unido: Cambridge University Press, 323 pp. Mathias Poertner. 2024. Creating Partisans: The Organizational Roots of New Parties in Latin America. Cambridge, Reino Unido: Cambridge University Press, 272 pp. Nancy L. Rosenblum y Russell Muirhead. 2024. Ungoverning: The Attack on the Administrative State and the Politics of Chaos. Princeton, New Jersey: Princeton University Press, 280 pp. Eric Storm. 2024. Nationalism: A World History. Princeton, New Jersey: Princeton University Press, 512 pp. Sten Rynning. 2024. Nato: From Cold War to Ukraine, a History of the World’s Most Powerful Alliance. New Haven: Yale University Press, 368 pp. Hendrik Simon. 2024. A Century of Anarchy? War, Normativity, and the Birth of Modern International Order. Nueva York: Oxford University Press, 432 pp. Catherine De Vries, David Doyle, Hector Solaz y Katerina Tertytchnaya. 2024. Money Flows: The Political Consequences of Migrant Remittances. Nueva York: Oxford University Press, 240 pp. Rosa María Mirón Lince (coord.). 2024. Los estados en 2022. La nueva distribución partidista, Ciudad de México: Facultad de Ciencias Políticas y Sociales, UNAM, 339 pp. Valeria Olvera Alvarado (coord.). 2024. Política Internacional. Temas de análisis 11. Edición de Edmundo Hernández-Vela Salgado. Ciudad de México: Facultad de Ciencias Políticas y Sociales, UNAM, 408 pp. Héctor Raúl Solís Gadea, Melissa Amezcua Yépiz y José María Casco (coords.). 2024. Democracias en disputa. Diagnósticos, narrativas y resistencias en América Latina. Coordinado por Valeria Olvera Alvarado. 2024. Buenos Aires: Política Internacional. Temas de análisis 11, Clacso, 420 pp.